Vegetative reactivity in athletes in a state of overtraining - Larysa Ruban; Oleksandr Khatsaiuk; Oleh Yareshchenko; Artem Korolov; Viacheslav Olenchenko (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to determine the state of the autonomic regulation of heart rhythm in athletes at various stages of overtraining from the results of an analysis of heart rate variability. Material & Methods: under our supervision there were 49 athletes with signs of overtraining of the I-II stage. To determine vegetative reactivity, an analysis of cardiointervalography data with an orthostatic test was performed. Results: revealed that the most often overtraining of the II stage was found among athletes of playing sports, and with athletic qualifications more often occurs among athletes of the I category than among masters of sports. The results of cardiointervalography indicated that in highly qualified athletes in a state of overtraining, the index of autonomic reactivity does not bring the value of the stress index beyond the balanced work of the ANS. In athletes from the 1st category, compared with masters of sports, hypersympathicotonic activity of the ANS occurs against the background of overtraining. Conclusions: a high indicator of the stress index after an orthostatic test indicates the development of the strain of autonomic and regulatory systems in the body of athletes of the first category, which can lead to a breakdown in the adaptive capabilities of the body.